203 Ticagrelor and Clopidogrel Attenuate the Prothrombotic State induced by Bacterial Endotoxaemia. (6th June 2015) - Thomas, Mark; Ajjan, Ramzi; Phoenix, Fladia; Outteridge, Samuel; Dockrell, David; Sabroe, Ian; Storey, Robert
Abstract : Introduction: In the PLATO study, the novel platelet P2Y12 inhibitor ticagrelor was unexpectedly associated with fewer deaths following pulmonary infections and sepsis than clopidogrel. The risk of myocardial infarction or stroke is greatly increased following bacteremia, which can create an inflammatory environment associated with thrombotic changes in the fibrin network. We therefore aimed to determine whether greater P2Y12 inhibition by ticagrelor compared to clopidogrel would result in greater reduction in platelet-leukocyte interactions, thereby reducing inflammatory responses and the prothrombotic state associated with inflammation. Methods: Thirty healthy volunteers were randomised to ticagrelor 90 mg bd (n = 10), clopidogrel 75 mg od (n = 10) or no antiplatelet medications (controls; n = 10) for one week. E. coli endotoxin (LPS) 2 ng/kg was then administered intravenously. Plasma fibrin clot density was assessed ex vivo using a validated turbidimetric assay and D-dimer was measured using the INNOVANCE assay. Fibrin clot structure was investigated ex vivo using scanning electron microscopy. Fibrin network density and fibrin diameter were determined using imageJ software. Informed consent was obtained. The study was approved by a medical ethics committee and funded by the Medical Research Council (UK). Results: In the control group, fibrin clot maximum absorbance (an indicator of fibrin clot density), increased by 109 ± 37% at 6 h after LPS administration compared to baseline (p < 0.001). The percentage increase in maximum absorbance was significantly lower in the ticagrelor group (33 ± 19%; p = 0.02) compared to control, but was not significantly lower in the clopidogrel group (67 ± 20%; p = 0.20). Scanning electron microscopy showed that the fibrin network density increased following LPS in the control group, whilst fibrin fibre diameter decreased (both p < 0.05). These changes are known to be prothrombotic and confer resistance to fibrinolysis. Ticagrelor significantly attenuated changes in both fibrin network density and fibre diameter (both p < 0.05), whereas clopidogrel did not have a significant effect. In the control group, plasma levels of the fibrin degradation product D-dimer increased from 192 ± 36 µg/l at baseline to a peak of 2, 217 ± 447 µg/l at 4 h after LPS (p < 0.001). Peak levels of D-dimer were 48% lower in the ticagrelor group (p < 0.001) and 31% lower in the clopidogrel group (p = 0.01) compared to control. Conclusion: To our knowledge, this is the first study to show that ticagrelor reduces prothrombotic changes in fibrin clot structure induced by bacterial endotoxaemia in vivo . The greater potency of the effects of ticagrelor compared to clopidogrel provides a potential mechanism for the reduced mortality following sepsis observed in the PLATO study.